Temporal Changes on the Risks and Complications of Posttransplantion Diabetes Mellitus Following Cardiac Transplantation - Nadia Iannino; Amine Nasri; Agnès Räkel; Anique Ducharme; Kim Lachance; Normand Racine; Simon de Denus; Maxime Tremblay-Gravel; Annik Fortier; Michel White (Journal of Transplantation)
Background. Recent changes in the demographic of cardiac donors and recipients have modulated the rate and risk, associated with posttransplant diabetes mellitus (PTDM). We investigated the secular trends of the risk of PTDM at 1 year and 3 years after transplantation over 30 years and explored its effect on major outcomes. Methods. Three hundred and three nondiabetic patients were followed for a minimum of 36 months, after a first cardiac transplantation performed between 1983 and 2011. Based on the year of their transplantation, the patients were divided into 3 eras: (1983-1992 [era 1], 1993-2002 [era 2], and 2003-2011 [era 3]). Results. In eras 1, 2, and 3, the proportions of patients with PTDM at 1 versus 3 years were 23% versus 39%, 21% versus 26%, and 33% versus 38%, respectively. Independent risk factors predicting PTDM at one year were recipient’s age, duration of cold ischemic time, treatment with furosemide, and tacrolimus. There was a trend for overall survival being worse for patients with PTDM in comparison to patients without PTDM (p = 0.08). Patients with PTDM exhibited a significantly higher rate of renal failure over a median follow-up of 10 years (p = 0.03). Conclusion. The development of PTDM following cardiac transplantation approaches 40% at 3 years and has not significantly changed over thirty years. The presence of PTDM is weakly associated with an increased mortality and is significantly associated with a worsening in renal function long-term following cardiac transplantation.